From global language use to local meanings: Arabic to Indonesian absorption - Muassomah, Muassomah (IAS Journal of Localities, 2023)
Arabic being one of the oldest languages in the world, has made significant contributions to other languages including Indonesian. Some Indonesian vocabulary along with its development has been adopted from Arabic. This paper not only aims to map the absorption words in various categories, but also to analyze the factors of Arabic absorption into Indonesian. Descriptive qualitative method is used to explore the data in the text. The data is analyzed in four stages: data reduction, data display, data verification, and conclusion drawing. This study shows that the adoption of Arabic into Indonesian tends to be on words related to Islam, which relate to function, morality, death, and the occult. The language absorption cannot be separated from the history of Islam in Indonesia as the language of Islam (Arabic) colors Indonesian culture. Further research can sharpen the semantic analysis because the absorbed words experience reduction and degradation of meaning.